THE PRACTICE OF KEJAWEN RITUALS THROUGH NGEBLENG FASTING - Solikhah, Amirotun; Saputro , Dedy Riyadin (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
Using a phenomenological approach, this study aims to reveal the psychological and social impact on three Ngebleng fasting performers in Kutasari village, Cipari district, and Cilacap district. Documentation and in-depth interviews are the main instruments for extracting as much information as possible and then interpreting it based on the phenomena obtained. The results showed that the psychological impact felt by fasting performers included inner peace, less emotional stress, and healthier physical conditions. Meanwhile, the social effects felt by the ritual actors varied. One perpetrator admitted that after undergoing Ngebleng fasting, he felt the smoothness of rizki and the establishment of good social relations; his fortune was smoother and social relations were not disturbed. Still, two people admitted that when fasting, they became less enthusiastic about interacting with the surrounding community because, apart from feeling weak physically, there were also considerations of maintaining so that the fast does not fail.